Porcentagem de sacarose aparente e potencial produtivo de açúcar em cultivares de cana - Hélio Francisco Da Silva Neto; Fernando Abackerli De Pauli; Luiz Carlos Tasso Junior; Marcos Omir Marques (Scientia Agropecuaria, 2014)
The percentage ofsaccharose apparent "POL" is an important variable for the determination of sugarproduction, and its value differs among the cultivars, plant parts and growth seasons. The study aimed tocompare values of POL and estimate productive potential of sugar injuice extracted from nodes andinternodes of the sugarcane cultivars sugar during the 2010/2011 crop season.We used the experimentaldesign of randomized blocks in factorial scheme 3x2x6, with four replications. The main treatments werecultivars of sugarcane, the secondary treatments two parts of the stalks of sugarcane, and third the seasons ofanalysis distributed over the harvest. The cultivars RB72454 and SP81-3250 showed the highest values POL.Conversely, the RB867515 obtained less satisfactory results, showing lower value of POL throughout thestudy period, and the two parts of the stalk. The internode was greater than POL, and showed greater potentialfor sugar production when compared to the stalk portion represented by the node. The values of POLand theproductive potential of sugar, obtained by both sides of the stalk were growing throughout the season, andcoincided with the harvest season recommended for these cultivars. However, there was this period that thebiggest difference between the parts of the stalk, indicating the need for a better use of the internode